ZO-1 and -2 Are Required for TRPV1-Modulated Paracellular Permeability. (December 2015) - Li, J.; Cong, X.; Zhang, Y.; Xiang, R.L.; Mei, M.; Yang, N.Y.; Su, Y.C.; Choi, S.; Park, K.; Zhang, L.W.; Wu, L.L.; Yu, G.Y.
The tight junction–based paracellular pathway plays an important role in saliva secretion. Zonula occludens (ZO) proteins are submembranous proteins of tight junction complex; however, their function in salivary epithelium is poorly understood. Here, we found that activation of transient receptor potential vanilloid subtype 1 (TRPV1) by capsaicin increased rat saliva secretion both in vivo and ex vivo. Meanwhile, TRPV1 activation enlarged the width of tight junctions between neighboring acinar cells, increased the paracellular ﬂux of 4-kDa fluorescein isothiocyanate (FITC)-dextran in submandibular gland (SMG) tissues, and decreased transepithelial electric resistance (TER) in SMG-C6 cells. ZO-1, -2, and -3 were distributed principally to the apical lateral region of acinar cells in SMG tissues and continuously encircled the peripheries of SMG-C6 cells in the untreated condition. TRPV1 activation obviously diminished ZO-1 and -2 staining, but not ZO-3 or β-catenin, at the cell-cell contacts ex vivo and in vitro. Moreover, in untreated SMG-C6 cells, ZO-1 and -2 single or double knockdown by small interfering RNA (siRNA) increased the paracellular ﬂux of 4-kDa FITC-dextran. In capsaicin-treated cells, ZO-1 and -2 single or double knockdown abolished, whereas their re-expression restored, the capsaicin-induced increase in paracellular permeability. Furthermore, TRPV1 activation increased RhoA activity, and inhibition of either RhoA or Rho kinase (ROCK) abolished the capsaicin-induced TER decrease as well as ZO-1 and -2 redistribution. These results indicate that ZO-1 and -2 play crucial roles in both basal salivary epithelial barrier function and TRPV1-modulated paracellular transport. RhoA-ROCK signaling pathway is responsible for TRPV1-modulated paracellular permeability as well as ZO-1 and -2 redistribution.